Liberty Laundry 1930s fleet - Pickford, Joel:::::::::
Liberty Laundry east building with its fleet of delivery trucks, 1930s. George Pickford is seen in the dark doorway. His sons, Rollin A. Pickford Sr., left (the artist's son) and William O. Pickford, right are seen shaking hands. George was the senior company manager, Rollin Sr. was the company's salesman, and William was the engineer. The laundry served private homes and larger clients such as hotels, boarding houses, restaurants, and undoubtedly, some of Fresno's many brothels of the era. The business closed permanently in the early years of World War II due to a labor shortage and the advent of affordable home washing machines. The second image is a closeup detail of the principals.